Critical Role of TGF-β and IL-2 Receptor Signaling in Foxp3 Induction by an Inhibitor of DNA Methylation - Freudenberg, Kristin; Lindner, Nadja; Dohnke, Sebastian; Garbe, Annette I.; Schallenberg, Sonja; Kretschmer, Karsten (Frontiers in Immunology, 2018)
Under physiological conditions, CD4+ regulatory T (Treg) cells expressing the transcription factor Foxp3 are generated in the thymus [thymus-derived Foxp3+ Treg (tTregs) cells] and extrathymically at peripheral sites [peripherally induced Foxp3+ Treg (pTreg) cell], and both developmental subsets play non-redundant roles in maintaining self-tolerance throughout life. In addition, a variety of experimental in vitro and in vivo modalities can extrathymically elicit a Foxp3+ Treg cell phenotype in peripheral CD4+Foxp3− T cells, which has attracted much interest as an approach toward cell-based therapy in clinical settings of undesired immune responses. A particularly notable example is the in vitro induction of Foxp3 expression and Treg cell activity (iTreg cells) in initially naive CD4+Foxp3− T cells through T cell receptor (TCR) and IL-2R ligation, in the presence of exogenous TGF-β. Clinical application of Foxp3+ iTreg cells has been hampered by the fact that TGF-β-driven Foxp3 induction is not sufficient to fully recapitulate the epigenetic and transcriptional signature of in vivo induced Foxp3+ tTreg and pTreg cells, which includes the failure to imprint iTreg cells with stable Foxp3 expression. This hurdle can be potentially overcome by pharmacological interference with DNA methyltransferase activity and CpG methylation [e.g., by the cytosine nucleoside analog 5-aza-2′-deoxycytidine (5-aza-dC)] to stabilize TGF-β-induced Foxp3 expression and to promote a Foxp3+ iTreg cell phenotype even in the absence of added TGF-β. However, the molecular mechanisms of 5-aza-dC-mediated Foxp3+ iTreg cell generation have remained incompletely understood. Here, we show that in the absence of exogenously added TGF-β and IL-2, efficient 5-aza-dC-mediated Foxp3+ iTreg cell generation from TCR-stimulated CD4+Foxp3− T cells is critically dependent on TGF-βR and IL-2R signaling and that this process is driven by TGF-β and IL-2, which could either be FCS derived or produced by T cells on TCR stimulation. Overall, these findings contribute to our understanding of the molecular mechanisms underlying the process of Foxp3 induction and may provide a rational basis for generating phenotypically and functionally stable iTreg cells.